Wear Behaviour Of A-C: H Helical Gear Through Particle Generation - Mat Dan, Reduan; Putra, Azma; Sudin, Mohd Nizam; Abdul Hamid, Abdul Hakim; Mazlan, Rozdman Khaidir (Science and Technology Research Institute for Defence, 2019)
This paper presents the wear performance of amorphous hydrogenated carbon (a-C:H) deposited on helical gears through wear debris analysis. Helical gears are tested on a power recirculating test rig with constant loads of 100 Nm and speed of 1,000 rpm. The tests are conducted for 9 million cycles or an initial pitting of 25% covering the surface of the teeth. Samplings are obtained for approximately 60 ml of the lubricant for every 3.6×105 cycles, which are then analysed through oil analysis that includes wear debris analysis as well as particle counting. The results reveal that the a-C:H coated gear reduces the particle generation by a factor of 3.11 as compared to the baseline testing. However, a-C:H does not affect the condition of the lubricant. It is found that the a-C:H gear had reduction in micro-pitting formation as compared to the uncoated gear. This study demonstrates an extension of the life of gears through the application of a-C:H coating.